2013
DOI: 10.1128/jvi.02682-12
|View full text |Cite
|
Sign up to set email alerts
|

The Hemagglutinin Protein of Highly Pathogenic H5N1 Influenza Viruses Overcomes an Early Block in the Replication Cycle To Promote Productive Replication in Macrophages

Abstract: Macrophages are known to be one of the first lines of defense against influenza virus infection. However, they may also contribute to severe disease caused by the highly pathogenic avian (HPAI) H5N1 influenza viruses. One reason for this may be the ability of certain influenza virus strains to productively replicate in macrophages. However, studies investigating the productive replication of influenza viruses in macrophages have been contradictory, and the results may depend on both the type of macrophages use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 39 publications
7
63
1
Order By: Relevance
“…The results demonstrated that HPAI H5N1 IAV is unique in its ability to replicate productively in macrophages. In contrast to what has been shown for human AMs, primary mouse AMs were also shown to support productive replication of HPAI H5N1, but not an H1N1 virus [39]. A comparison of the replication of 23 different IAV strains of different HA subtypes in RAW264.7 cells also showed that HPAI H5N1 viruses and the H1N1 WSN strain were the only viruses that could productively replicate.…”
Section: Replication Of Iav In Macrophagescontrasting
confidence: 76%
See 3 more Smart Citations
“…The results demonstrated that HPAI H5N1 IAV is unique in its ability to replicate productively in macrophages. In contrast to what has been shown for human AMs, primary mouse AMs were also shown to support productive replication of HPAI H5N1, but not an H1N1 virus [39]. A comparison of the replication of 23 different IAV strains of different HA subtypes in RAW264.7 cells also showed that HPAI H5N1 viruses and the H1N1 WSN strain were the only viruses that could productively replicate.…”
Section: Replication Of Iav In Macrophagescontrasting
confidence: 76%
“…PR8 also failed to productively replicate in RAW264.7 cells. The restriction of PR8 in RAW264.7 cells has been linked to inefficient attachment and entry [27] and to a block downstream of virus internalization but upstream of nuclear entry [32,39]. The differences in the results presented by these investigators may be attributed to differences in the preparation or source of the exact PR8 virus used in the studies.…”
Section: Mechanism Of Iav Restriction In Macrophagesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies looking at IAV-MDM interactions used the 1ug/ml TPCK trypsin concentration [222,353,391] and since we did not see a difference between 0.5 and 1ug/ml we decided to move forward using 1ug/ml so we could best compare our results to others. Here we compared influenza isolates derived in eggs to those derived in cell cultures to determine if there was a difference in activation and their ability to infect MDM.…”
Section: Optimization Of the Iav-mdm Infection Protocolmentioning
confidence: 99%